Stem Cell and Neural Progenitor Cell Therapy for Neurogenic Bladder—Where Are We in 2023? - Isali, Ilaha; Wong, Thomas R.; Hijaz, Adonis (Current bladder dysfunction reports, 2024)
Purpose of Review This review aims to consolidate the currently available literature regarding the treatment of neurogenic bladder (NGB) with stem cells or neural progenitor cells (NPCs). Recent Findings Several promising studies published in the past 5 years suggest therapeutic potential of stem cells in treating NGB. In vitro models of NGB have demonstrated the efficacy of stem cells from varying sources to induce nerve regeneration while simultaneously improving bladder function parameters. Additionally, mesenchymal stem cells (MSCs) were found to inhibit fibrosis through the TGF-β1 signaling pathway while their effects were potentiated by elevated levels of BDNF or SDF-1. Among induced pluripotent stem cells (iPSCs), it was noted that autophagy inducers improved regenerative effects. NPCs, in a recent clinical trial, also underscored the potential for translating stem cell therapies into practice. Summary Stem cells offer a potentially revolutionary regenerative medicine strategy for treatment of NGB. Many in vivo trials are promising, but there is a distinct shortage of clinical trials attempting to translate this success into human subjects. In the future, research should be directed towards understanding the complex mechanisms of stem cell-based therapy while moving towards the clinical applications of the technology.